Multidisciplinary Collaboration In Diagnosing And Managing Complex Chronic Infections (The Review of Diabetic Studies, 2024)
Infections have been linked to acute and chronic kidney diseases. This review considers the etiology, epidemiology, and molecular mechanisms underlying chronic infection-induced renal injury and the range of clinical presentations that occurs, including glomerulonephritis, interstitial nephritis, pyelonephritis, and amyloidosis. The role of infection in development of renal disease is often difficult to prove, particularly in chronic cases, where relationships can be indirect and prolonged. A multidisciplinary approach is essential in establishing the cause and managing chronic renal infections. Chronic infections can result from a range of microbial etiologies, produce mild and non-specific clinical symptoms, and damaging immune-mediated mechanisms. Consequently, microbial infection is sometimes invoked as a potential initiating or perpetuating pathology in cases in which disease processes are not yet fully understood. While a definitive pathological role for causal microbial agents remains to be established in many chronic conditions, neuroradiological imaging and pathological evidence have highlighted associations, emphasizing the need for multidisciplinary engagement in diagnosis and treatment. The potentially damaging effect of such infections on the nervous system and other vital physiological processes, including renal function, requires urgent consideration (L. Romanò et al., 2022). Interdisciplinary teams are essential in the diagnosis, management, and prevention of complex infections including those with neurological and renal consequences. Specialist teams are commonplace in prosthetic joint infections because of the complexity that arises from multifaceted diagnostic and treatment protocols. Such teams typically involve collaboration between Orthopaedic, Infectious Disease, Microbiology, allied health, and nursing departments to improve patient care (Sires et al., 2022). Management of complex neurological infections requires collaborative consideration among surgical specialties related to the site and type of infection, the likelihood of progression, and potential neurological sequelae. Non-surgical teams involved in diagnosis and treatment may include Diagnostic and Interventional Radiology, Infectious Diseases, Microbiology, Neurology, and Nephrology (Therese R. Madelar & Ito, 2023). Multidisciplinary teams also consider macroscopic and microscopic characteristics of the host, which may dictate an operative, device retention, suppressive, or palliative medical management strategy to provide the best patient outcome.